Noong unang panahon - Valera, Rafaelita S. (Quezon City, Philippines : Adarna House Inc., 2005)
How was the world created? Where did man come from? Read three legends, from the Samal, Ifugaw, and Tagalog and Visayan, that explain the origins of the world and mankind.
Keywords: FICTION STORY